Castleman disease of stomach treated by endoscopic submucosal dissection: a case report and literature review - Sun, Ting-Ting; Sun, Xue-Guo; Shan, Ti-Dong; Zhao, Peng; Lu, Yan-Yan; Li, Qian; Liu, Fu-Guo (Frontiers in Oncology, 2025)
BackgroundCastleman disease (CD) is a relatively rare benign lymphoproliferative disorder of the lymphoid tissue. According to clinical manifestations, it is classified into two types: unicentric CD (UCD) and multicentric CD (MCD). Pathological subtypes include hyaline-vascular (HV), plasma cell (PC), and mixed (MV). Gastrointestinal CD is extremely rare, and limited information is available regarding its clinical presentation and management.Case SummaryWe report a case of a patient who presented with paroxysmal epigastric pain for 4 years. Laboratory tests showed no remarkable abnormalities, whereas CT revealed endogenous occupancy on the side of the greater curvature of the stomach. Ultrasonographic endoscopy demonstrated hypoechoic, well-defined foci. The lesion initially suspected to be an inflammatory fibroma was subsequently pathologically confirmed as HV-UCD following endoscopic submucosal dissection. The lesion was completely resected, and the patient showed no signs of recurrence during 7 months of follow-up.ConclusionGastrointestinal CD is rare and should be differentiated from other occupying lesions. Its definitive diagnosis relies on histopathology.